Cryptocurrency and financial innovation: unveiling the motivators behind cryptocurrency investment intentions in Malaysia - Hosen, Mosharrof; Sia, Sui King; Ooi, Hui Ting; Mohd Thas Thaker, Hassanudin (Scrivener Publishing Wiley, 2025)
Despite the abundance of studies examining cryptocurrency acceptance and price dynamics, there is a notable gap in empirical research focused specifically on individual inclinations to adopt cryptocurrency in Malaysia. Most existing research has concentrated on developed economies leaving a void in our understanding of the Malaysian market. This chapter aims to address this gap by identifying the key factors influencing Malaysians’ willingness to adopt cryptocurrency utilizing the framework of the “Unified Theory of Acceptance and Use of Technology 2." The sampling was based on judgment, and there were 200 usable responses. The results of SmartPLS indicate that the five factors—government regulations, perceived risk, value for money, societal influence, and trust—have a significant positive relationship with the cryptocurrency usage intention of Malaysians. However, the factor of habit did not show significant evidence of influence. These results carry some useful policy implications, which are discussed in due order.